Development of Corynebacterium glutamicum as staphylococcal-targeting chassis via the construction of autoinducing peptide (AIP)-responsive expression system - Ummul Syafiqah Ruslan,; Nurul Hanun Ahmad Raston,; Nur Azlina Mohd Sharif,; Neoh, Hui Min; Sheila Nathan,; Ahmad Bazli Ramzi, (penerbit Universiti Kebangsaan Malaysia, 2023)
Despite increasing reports of antimicrobial activities of commensal and non-pathogenic bacteria such as Corynebacterium spp., previous studies on bioengineered therapeutics traditionally employed probiotics and food-grade bacteria which limits further advancements into microbial therapeutics research. In this study, Corynebacterium glutamicum, a generally recognised as safe (GRAS) and model bacterium was employed as a new chassis for the development of bioengineered corynebacterial chassis tailored towards Staphylococcus sp. via autoinducer peptide (AIP)-based quorum sensing (QS) interactions. To develop C. glutamicum as a staphylococcal-targeting chassis, the bacteria were transformed with the pResponse plasmid harboring AIP-responding accessory regulatory proteins agrAC and red fluorescent protein (RFP) genes under the control of the PaceA and P3 promoter, respectively, which was expected to stimulate the production of fluorescence signals in the presence of AIPs. Fluorescence activity of the C. glutamicum pResponse strain was compared to control C. glutamicum pRFP strain containing only the P3-RFP gene without the agrAC gene cassette. Using AIP-I as the input biomolecule, C. glutamicum pResponse strain fluoresced under different concentrations of AIP-I whereas no fluorescence was observed in the control C. glutamicum pRFP strain. When tested with S. aureus culture supernatant, the pResponse strain exhibited increasing fluorescence over the incubation period with the highest fluorescence signal of 183 relative fluorescence units (R.F.U) was observed at the 48 h point thereby demonstrating a functional QS-responsive protein expression system in bioengineered C. glutamicum. These findings demonstrated the feasibility and promising potential of developing bioengineered C. glutamicum as a staphylococcalresponsive and -targeting chassis.